Costs and cost-effectiveness of Shamiri, a brief, layperson-delivered intervention for Kenyan adolescents: a randomized controlled trial - Corinne N. Kacmarek; Natalie E. Johnson; Tom L. Osborn; Christine Wasanga; John R. Weisz; Brian T. Yates (BMC Health Services Research, 2023)
Abstract Background Low- and middle-income countries (LMICs) have the highest socio-economic burden of mental health disorders, yet the fewest resources for treatment. Recently, many intervention strategies, including the use of brief, scalable interventions, have emerged as ways of reducing the mental health treatment gap in LMICs. But how do decision makers prioritize and optimize the allocation of limited resources? One approach is through the evaluation of delivery costs alongside intervention effectiveness of various types of interventions. Here, we evaluate the cost-effectiveness of Shamiri, a group– and school–based intervention for adolescent depression and anxiety that is delivered by lay providers and that teaches growth mindset, gratitude, and value affirmation. Methods We estimated the cost-effectiveness of Shamiri using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) guidelines for economic evaluations. Changes in depression and anxiety were estimated using the Patient Health Questionnaire (PHQ-8) and Generalized Anxiety Disorder questionnaire (GAD-7) at treatment termination and 7-month follow-up using two definitions of treatment benefit. Cost-effectiveness metrics included effectiveness-cost ratios and cost per number needed to treat. Results Base case cost assumptions estimated that delivering Shamiri cost $15.17 (in 2021 U.S. dollars) per student. A sensitivity analysis, which varied cost and clinical change definitions, estimated it cost between $48.28 and $172.72 to help 1 student in Shamiri, relative to the control, achieve reliable and clinically significant change in depression and anxiety by 7-month follow-up. Conclusions Shamiri appears to be a low-cost intervention that can produce clinically meaningful reductions in depression and anxiety. Lay providers can deliver effective treatment for a fraction of the training time that is required to become a licensed mental health provider (10 days vs. multiple years), which is a strength from an economic perspective. Additionally, Shamiri produced reliable and clinically significant reductions in depression and anxiety after only four weekly sessions instead of the traditional 12–16 weekly sessions necessary for gold-standard cognitive behavioral therapy. The school setting, group format, and economic context of a LMIC influenced the cost per student; however, broader conclusions about the cost-effectiveness of Shamiri have yet to be determined due to limited economic evaluations of mental health programs in LMICs. Trial registration This study was registered prior to participant enrollment in the Pan-African Clinical Trials Registry (PACTR201906525818462), registered 20 Jun 2019, https://pactr.samrc.ac.za/Search.aspx .